Applying Graph Coloring To Schedule Doctors' Work In A Hospital. - Taoufic, Ferdous Omar (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
Scheduling shifts is a tiresome and time consuming task in any business, and particularly in hospitals where errors are costly, rules are plentiful and changes are rapid. The person performing this function (Rota Organizer) will have to keep track of all the employees concerned, distributing hours fairly and avoiding collisions. Rules regulating working hours and breaks have to be followed and the qualifications of individual employees need to be considered. Hours are spent every day on this task in every ward. The goal of this paper is to solve Doctors Scheduling Problem (DSP) and initialize a fair roster for two wards of Pediatric Department (PD) in Prince Sultan Military Medical City (PSMMC) in Saudi Arabia. So to find a solution of DSP, we used Graph Coloring which is one of the methods used mostly to solve this problem.